2002
DOI: 10.1095/biolreprod66.6.1734
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase Alpha Expressed in Porcine Sertoli Cells Is under the Control of Follicle-Stimulating Hormone and Testosterone1

Abstract: Glutathione S-transferases (GSTs) are a family of detoxification isoenzymes present in different tissues including the testis and that conjugate many toxic substrates to glutathione. Among these substrates are carcinogens, mutagens and products of oxidative processes. In the present report we show that GSTalpha is expressed in somatic testicular Leydig cells and Sertoli cells. GSTalpha expression in Sertoli cells is under the hormonal control of FSH, testosterone, and estradiol. In Leydig cells, immunoreactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Protein extracts (80 mg/well for GSTa, 100 mg/well for AR) were size fractionated on SDSpolyacrylamide gel (Benbrahim-Tallaa et al 2002b). The membranes were incubated with the rabbit polyclonal antiGSTa antibody diluted 1:1000 or the rabbit polyclonal anti-AR antibody diluted 1:100 in a solution of tris buffered saline (TBS) with 0 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein extracts (80 mg/well for GSTa, 100 mg/well for AR) were size fractionated on SDSpolyacrylamide gel (Benbrahim-Tallaa et al 2002b). The membranes were incubated with the rabbit polyclonal antiGSTa antibody diluted 1:1000 or the rabbit polyclonal anti-AR antibody diluted 1:100 in a solution of tris buffered saline (TBS) with 0 .…”
Section: Methodsmentioning
confidence: 99%
“…This gene is expressed in both Leydig and Sertoli cells (Benbrahim-Tallaa et al 2002b) and was reported to be under the control of androgens in Sertoli cells (Benbrahim-Tallaa et al 2002b). In utero flutamide treatment resulted in a decrease in GSTa mRNA levels in seminiferous tubules with a significant decrease observed at 2 mg/kg d (PZ0 .…”
Section: Effects Of In Utero Exposure To Flutamide On Sertoli Cell Gementioning
confidence: 97%
“…[91][92][93] Levels of these GSHsynthesizing enzymes can be altered by both estrogens 94,95 and testosterone. 96,97 GSH is typically reduced under conditions of enhanced oxidative stress due to the enhanced destruction of GSH in the process of neutralizing free radicals. 98,99 Estrogens appear to have direct potent antioxidant activity, 100,101 and so may prevent the early decline in GSH that occurs in males by contributing to antioxidant defense.…”
Section: Glutathionementioning
confidence: 99%
“…Less is known about GST regulation by hormones. Adrenocorticotrophic hormone (39), glucocorticoids (19, 33), growth hormones (54), thyroid hormones (TH) (6,11,31), and sex steroids (7,25,30) are able to modulate GST.Thyroid hormones, including thyroxine (T 4 ) and triiodothyronine (T 3 ), are essential during embryonic development and play critical roles in several physiological processes in adult organisms (36). It is agreed that most of the TH effects are mediated by nuclear action via a superfamily of ligand-modulated transcription factors that modify target gene transcription (36).…”
mentioning
confidence: 99%